QRIS AND CHANGES IN STUDENT PAYMENT PATTERNS: A QUALITATIVE STUDY OF FKIP UMS STUDENTS - Mohammad Rafly Hatami; Suranto (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to gain an in-depth understanding of the phenomenon of using the Quick Response Code Indonesian Standard (QRIS) among students as well as the factors influencing its adoption and continued use. This research employs a descriptive qualitative approach, with data collected through in-depth interviews, participatory observation, and documentation involving active student users of QRIS and merchants around the campus. The findings reveal that convenience, speed, and cross-platform capability are the main factors driving students to use QRIS. Incentives such as cashback and discounts also play an important role as initial motivations for adoption. However, the sustainability of QRIS usage is significantly affected by users’ trust levels and experiences. Negative experiences such as failed transactions, network disruptions, and security risks reduce students’ willingness to continue using QRIS. Furthermore, the use of QRIS has a dual impact on students’ financial behavior: on one hand, it increases consumptive tendencies, while on the other, it helps financially literate students control their expenses through digital transaction records. External factors such as limited internet connectivity and merchant readiness also serve as major barriers to sustained use. Therefore, enhancing students’ financial and digital literacy, providing technical training for small merchants, and strengthening network infrastructure are essential to support the sustainable, secure, and inclusive implementation of QRIS within the university environment.